2020
DOI: 10.1111/tri.13591
|View full text |Cite
|
Sign up to set email alerts
|

Donor cardiac arrest and cardiopulmonary resuscitation: impact on outcomes after simultaneous pancreas–kidney transplantation – a retrospective study

Abstract: Donor cardiac arrest and cardiopulmonary resuscitation (CACPR) has been considered critically because of concerns over hypoperfusion and mechanical trauma to the donor organs. We retrospectively analyzed 371 first simultaneous pancreas-kidney transplants performed at the Medical University of Innsbruck between 1997 and 2017. We evaluated short-and long-term outcomes from recipients of organs from donors with and without a history of CACPR. A total of 63 recipients received a pancreas and kidney graft from a CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…8-10 Therefore, after thorough donor evaluation, a history of CPR alone is no longer considered a contraindication for organ donation in most institutions. 11-15…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8-10 Therefore, after thorough donor evaluation, a history of CPR alone is no longer considered a contraindication for organ donation in most institutions. 11-15…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] Therefore, after thorough donor evaluation, a history of CPR alone is no longer considered a contraindication for organ donation in most institutions. [11][12][13][14][15] However, cardiac arrest in avalanche victims is predominately due to asphyxia, and data obtained from patients with primary cardiac arrest may not be extrapolated to this scenario involving suffocation and prolonged hypoxia. Organs from donors with a history of asphyxia, such as from hanging or drowning, have long been considered high risk for transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Nonetheless, on average, resuscitated CA does not impair allograft function in the recipient. 8,11,14-18 The favorable characteristics of these donors selected despite their history of CA might explain this result, as could the modification by other factors of the effects of ischemia in this situation. For example, experimental models show that a first ischemic episode can provide time-limited protection against a second injury, a phenomenon called ischemic preconditioning.…”
Section: Introductionmentioning
confidence: 95%
“…Donors’ renal function decreases after a resuscitated CA. 8,11 Other causes of warm ischemia during kidney transplantation, for example, vascular anastomosis time, also lead to poorer functional results. 12,13 Nonetheless, on average, resuscitated CA does not impair allograft function in the recipient.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that transplantation outcomes of donors who died due to brain death after ROSC are not bad compared to those of donors who have not undergone CPR. [200][201][202][203][204][205][206][207][208][209] Based on the results of published studies so far, it has been summarized that CPR does not affect outcomes of the transplanted organ. 210 Therefore, organ donation should be considered in comatose patients who ]fulfill neurological criteria for brain death after ROSC or cardiac arrest patients who have failed to ROSC from cardiac arrest.…”
Section: Organ Donationmentioning
confidence: 99%